Periodic and weakly periodic ground states for the λ-Model on Cayley tree - Mukhamedov, Farrukh; Pah, Chin Hee; Rahimatullaev, Muzaffar; Jamil, Hakim (Institute of Physics Publishing, 2018)
In this paper we consider the λ-model on the Cayley tree of order two. We describe the periodic and weakly periodic ground states for the considered model.